2010
DOI: 10.1088/0957-4484/21/50/505706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2nanotube parameters on field emission properties

Abstract: The dependence of field emission properties of titanium dioxide (TiO(2)) nanotubes (NTs) has been studied as a function of NT diameter (D) and height (h), which varied in the ranges 18-500 nm and 500-12,000 nm, respectively. The studies showed a strong dependence of the field emission on these parameters. With an increase of NT diameter, the field enhancement factor increased monotonically from 120 to 3800; the current density also increased until D = 320 (current density ∼ 3.8 mA cm( - 2)), with subsequent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…separation between nanotubes) and clusters appearance of the TiO 2 nanotubes array appear to create eld screening effects. 7 Moreover, the uncontrolled and random dispersion of TiO 2 nanowires 12 and nanorods 13 affect their FE adversely. Highly dense rutile TiO 2 hierarchical nanorods network arranged in the form of dandelion ower like morphology suffer from signicant eld screening effect thereby exhibiting poorer FE behavior.…”
Section: Introductionsmentioning
confidence: 99%
“…separation between nanotubes) and clusters appearance of the TiO 2 nanotubes array appear to create eld screening effects. 7 Moreover, the uncontrolled and random dispersion of TiO 2 nanowires 12 and nanorods 13 affect their FE adversely. Highly dense rutile TiO 2 hierarchical nanorods network arranged in the form of dandelion ower like morphology suffer from signicant eld screening effect thereby exhibiting poorer FE behavior.…”
Section: Introductionsmentioning
confidence: 99%
“…Over the past few years, considerable progress has been made in improving the FE of TNAs by various routes, particularly via optimizing nanotubular morphology of TiO 2 [21][22][23]. For example, Y. Alivov et al [24] discussed the effect of the diameter and length of TNAs on the FE current density and field enhancement factor. Y. Ye et al [25] investigated the influence of inter-cluster distance of TNAs on their FE properties and achieved an optimal result of turn-on field at 1.9 V/mm.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 NTs with a wide band gap (E g ) of $3.2 eV and a low work function (WF) of $4.4 eV, which have been widely synthesized and investigated, 5,6 have not only superior photocatalysis 7 but promising field-emission properties. 8 It has been demonstrated that the TiO 2 NTs grown vertically on a Ti substrate by electrochemical process exhibit a narrow distribution of electron kinetic energy, 9 where an excellent adherence can greatly lower the contact resistance at interfaces, and effectively improve the efficiency of electron emitting. In addition, the field emission behavior of TiO 2 with a high electron affinity 10,11 could be improved by introducing oxygen vacancies (V O 's) 8,12,13 or doping Fe (Ref.…”
mentioning
confidence: 99%